Can the subaltern speak? - Peñafiel Loaiza, Estefanía (Two works, 2020)
Essay "in dialogue" with specially comissioned artwork by artist Estefanía Peñafiel Loaiza.
Keywords: Peñafiel Loaiza, Estefanía, : 1978-; 2000-luku (vuosisata); Art, French : 21st century; Art, Ecuadorian : 21st century; Colonization in art; Decolonization in art; Postcolonialism : Philosophy; Decolonization : Philosophy; kolonialismi; dekolonisaatio; postkolonialismi; taide; filosofia; yhteiskuntafilosofia